Characterization of Contemporary Otolaryngology‐Specific Emergency Room Care at the Massachusetts Eye and Ear Infirmary. (2nd September 2014) - Sethi, Rosh K. V.; Kozin, Elliot D.; Remenschneider, Aaron K.; Lee, Daniel J.; Gray, Stacey T.; Shrime, Mark G.; Gliklich, Richard E.
Abstract : Objectives: (1) Characterize contemporary utilization patterns of a stand‐alone otolaryngology emergency room (ER). (2) Assess the range of otolaryngologic complaints. (3) Determine characteristics of patients that require inpatient admission. (4) Provide a practical discussion about the utility of a specialized ER in otolaryngologic care. Methods: Retrospective review of demographic and diagnostic data for all patients with an otolaryngologic complaint evaluated at our institutions ER from January 2011 through September 2013. Descriptive analysis was performed to characterize utilization and diagnostic patterns. Multivariable regression modeling was used to identify predictors of inpatient admission. Geocoding analysis was performed to characterize the ER catchment area. Results: A total of 12, 234 patient visits were evaluated. Mean patient age was 44.7 years with equal sex distribution. The majority of visits occurred during daytime hours (75%) with peak volume occurring mid‐day. Auditory and vestibular problems constituted the most frequent presenting complaints (50.0%). The majority of patients were discharged home (92.3%). Significant predictors of inpatient admission were pediatric designation (odds ratio [OR] 1.9, P <. 0001), male sex (OR 1.3, P <. 0001), arrival overnight (OR 3.3, P <. 0001), postoperative complaint (OR 7.3, P <. 0001), and laryngeal complaint (OR 2.4, P <. 0001). Median distance traveled was 9.6 miles. Patients traveled farther for evaluation of hearing loss (11 miles) and less far for common diagnoses including impacted cerumen (7.1 miles; P <. 0001). Conclusions: This study provides a contemporary analysis of patterns of specialized otolaryngology ER care in the United States. This study has broad implications for otolaryngology care and resource utilization in the emergency care setting.